Implementation of the North Industrial Center (CIN) in Feira de Santana, BA (Brazil): characteristics, changes and spatial interactions (Terr@ Plural, 2022)
This paper analyzes the changes in industrial activity in Feira de Santana, especially regarding the implantation of the Centro Industrial Norte (CIN), its characteristics and socioeconomic consequences. The Centro Industrial Subaé (CIS), the first in the city, was installed in the 1970s. However, over the years, there were interests to expand this dynamic to other areas, such as the Northern Sector, which was not the object of interventions, until then. The installation of the industries took place gradually, starting in 2010 at the CIN, and the choice of the area was due to the location, incentives and changes in the urban land use law. Industries maintain spatial interactions with other areas and this dynamic attracts new factories, in the context of flexible accumulation.
Keywords: Plants; urban land use law; Spatial interactions